2003
DOI: 10.1002/eji.200323693
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GD3 expression on target cells can modulate NK cell cytotoxicity via siglec‐7‐dependent and ‐independent mechanisms

Abstract: Siglec-7 is a sialic acid binding receptor with inhibitory potential, expressed on human NK cells and monocytes. It has an unusual binding preference for § 2,8-linked disialic acids, such as those displayed by ganglioside GD3. Here we have investigated whether siglec-7-GD3 interactions are able to modulate NK cell cytotoxicity. Using synthetic polyacrylamide glycoprobes, siglec-7 was found to be masked at the NK cell surface but it could be unmasked by sialidase treatment of NK cells. GD3 synthase-transfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
207
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(217 citation statements)
references
References 21 publications
7
207
0
1
Order By: Relevance
“…Although mSiglec-E does not exhibit any significant sequence similarity with hSiglec-7 in the C-C' loop, it possesses a cluster of three basic residues that could favor charge interactions with disialic acids (C-C' loop: TDRRKD). Recent studies in our laboratory have demonstrated that overexpressed GD3 (a ganglioside carrying § 2,8-linked disialic acid) on target cells binds to hSiglec-7 on human NK cells and contributes to the down-regulation of target cell killing [29]. Whether sialic acid engagement of mSiglec-E expressed on NK cells and monocytes is able to similarly modulate cellular function awaits future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Although mSiglec-E does not exhibit any significant sequence similarity with hSiglec-7 in the C-C' loop, it possesses a cluster of three basic residues that could favor charge interactions with disialic acids (C-C' loop: TDRRKD). Recent studies in our laboratory have demonstrated that overexpressed GD3 (a ganglioside carrying § 2,8-linked disialic acid) on target cells binds to hSiglec-7 on human NK cells and contributes to the down-regulation of target cell killing [29]. Whether sialic acid engagement of mSiglec-E expressed on NK cells and monocytes is able to similarly modulate cellular function awaits future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Cytotoxicity assays have shown that an interaction between Siglec-7, expressed on NK cells, and GD3, expressed on target cells, can down-modulate NK killing (21). It is speculated that Siglec-7 may perform a protective role, recognizing such ligands as markers of "self " and preventing inappropriate NK activation.…”
Section: Discussionmentioning
confidence: 99%
“…Siglec-7 is an inhibitory receptor expressed on NK cells and to a lesser extent, monocytes and a subset of CD8ϩ T cells (13,(17)(18)(19)(20)(21). In vitro binding studies have revealed that Siglec-7 shows a marked preference for glycoconjugates bearing ␣(2,8)-linked disialic acid and branched ␣(2,6)-linked sialic acid (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…сіалозв'язуючий лектин І типу сіглек 7 [2], беруть участь у регенерації мієлінового шару, взаємодіючи через мієлін асоційований глікопротеїн [1,3], можуть регулюва-ти активність рецепторів інсуліну та ЕФР, взаємодіючи із тирозинкіназними доме-нами [3,4], є лігандами, що розпізнаються різними токсинами прокаріот, а також можуть брати участь у розпізнаванні клітин макрофагами. Біосинтез гангліозидів [5], який у спрощеному вигляді представлено на рис.1, сприяє різноманітності мож-ливих гліканових ланцюгів цих молекул.…”
unclassified